Immune-Related Adverse Events Associated with Immune Checkpoint Inhibitors: A Narrative Clinical Review - Shahverdi, Ehsan; Abolghasemi, Hassan; Shahverdi, Amin; Kamali, Shadi; Hosseini, Seyed Mohammadsaber (Asian Pacific Journal of Cancer Biology, 2026)
Background: Immune checkpoint inhibitors (ICIs) have revolutionized cancer therapy by promoting durable tumor responses across multiple malignancies. However, by unleashing immune activation, these agents can trigger a broad spectrum of immune-related adverse events (irAEs) that may affect virtually any organ system. Objective: This review summarizes the current understanding of the mechanisms, clinical manifestations, diagnostic approaches, and management strategies of irAEs, and discusses emerging directions in research aimed at improving patient safety and treatment personalization. Methods: A comprehensive literature search was performed using PubMed and major oncology journals for studies published between 2018 and 2025. Keywords included immune-related adverse events, immune checkpoint inhibitors, management, pathophysiology, and clinical outcomes. Priority was given to randomized trials, systematic reviews, and international clinical practice guidelines (ASCO, ESMO, SITC). Results: irAEs arise from loss of immune self-tolerance and cytokine-mediated inflammation following ICI therapy. Commonly affected systems include dermatologic, gastrointestinal, hepatic, pulmonary, endocrine, and, less frequently, cardiac or neurologic organs. Severity ranges from mild, self-limiting reactions to life-threatening complications such as myocarditis or pneumonitis. Management is guided by toxicity grade, typically involving corticosteroids and, for refractory cases, biologic immunosuppressants such as infliximab, mycophenolate, or tocilizumab. Multidisciplinary management and patient education are vital for reducing morbidity. Emerging research focuses on predictive biomarkers, microbiome modulation, and the integration of artificial intelligence for early detection and monitoring. Conclusions: irAEs represent a mechanistically predictable but clinically complex consequence of immune activation. Prompt diagnosis and individualized management are essential to optimize safety without compromising therapeutic benefit.